Genetic variants of Grapevine leafroll-associated virus 2 infecting Portuguese grapevine cultivars - FONSECA, Filomena; ESTEVES, Filipa; TEIXEIRA SANTOS, Margarida; BRAZÃO, João; EIRAS-DIAS, José Eduardo (Phytopathologia Mediterranea, 2016)
Genetic variability of 19 isolates of Grapevine leafroll-associated virus 2 (GLRaV-2) from Portuguese grapevine cultivars was characterized by sequencing the entire capsid protein (CP) gene of the virus. Global phylogenetic analysis of the CP gene, which included nucleotide sequences obtained in this study and complete homologous sequences from GenBank, showed segregation of GLRaV-2 variants from Portuguese isolates into three major phylogroups (PN, 93/955 and H4). The novelty of these phylogenetic results is the evidence of well-supported subdivision within H4 as well as within PN, with subgroup PN3 composed exclusively of variants from a Portuguese isolate. These findings and the genetic analysis of global phylogroups indicate demographic expansion, mainly within PN and 93/955. Because the existence of a mixture of variants from different phylogroups was detected in some of the isolates, a typification assay based on reverse transcription reaction followed by polymerase chain reaction and restriction fragment length polymorphism analysis, was developed to complement molecular detection assay of the virus. This protocol discriminates variants from the phylogroups identified in this study, and is appropriate for routine testing for GLRaV-2.